Complications and neurologic deterioration after bilateral decompressive craniectomy in Gunshot penetrating brain injury in children. - Domínguez-Rojas, Jesus Ángel (2022)
Introduction: Penetrating skull injuries in pediatrics (TPC) occupy a special place due to their rarity. The aim is to provide an overview of the current evidence on decompressive craniectomy in children, to describe the indications and to detail the complications. Reporte case: We present the case of a 12-year-old boy who suffered a TPC by a projectile that perforated his head, causing multiple brain injuries, and underwent early bilateral decompressive craniectomy, presenting the complications and neurological disabilities typical of the injury and surgery, with a reserved evolution and prognosis. Conclusions: Pediatric penetrating skull injuries should be of individualized management, type of injury and disease, experience of the treatment team, and the decision should always be consensual in front of the benefits and risks in the short and long term.